2023
DOI: 10.3390/ijms24021156
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prenatal Dexamethasone Exposure on Brain Metabolic Homeostasis in Adulthood: Implications for Depression

Abstract: Since depression produces a long-term negative impact on quality of life, understanding the pathophysiological changes implicated in this disorder is urgent. There is growing evidence that demonstrates a key role for dysfunctional energy metabolism in driving the onset of depression; thus, bioenergetic alterations should be extensively studied. Brain metabolism is known to be a glucocorticoid-sensitive process, but the long-lasting consequences in adulthood following high levels of glucocorticoids at the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…As glucose metabolism supplies more than 95% of ATP in the brain, this may strongly suggests the intriguing possibility that decreased ATP level caused by mitochondrial disorders is critically involved in neurological diseases, including depression. 20,21 In the past decade, evidence from some patients with major depressive disorder (MDD) exhibits decreased glucose metabolism level in some brain regions related to emotion regulation, such as bilateral insula, left lentiform nucleus putamen and extra-nuclear, right caudate and cingulate gyrus. 22 Similarly, several studies have shown that the beta-nucleoside triphosphate, which arises from beta-ATP, is much lower in the basal ganglia of MDD patients.…”
Section: Mitochondrial Energy Me Tabolis M and Depre Ss Ionmentioning
confidence: 99%
See 4 more Smart Citations
“…As glucose metabolism supplies more than 95% of ATP in the brain, this may strongly suggests the intriguing possibility that decreased ATP level caused by mitochondrial disorders is critically involved in neurological diseases, including depression. 20,21 In the past decade, evidence from some patients with major depressive disorder (MDD) exhibits decreased glucose metabolism level in some brain regions related to emotion regulation, such as bilateral insula, left lentiform nucleus putamen and extra-nuclear, right caudate and cingulate gyrus. 22 Similarly, several studies have shown that the beta-nucleoside triphosphate, which arises from beta-ATP, is much lower in the basal ganglia of MDD patients.…”
Section: Mitochondrial Energy Me Tabolis M and Depre Ss Ionmentioning
confidence: 99%
“…In addition, it has been shown that prenatal Dex exposure results in depression-like behavior, accompanied by mitochondrial dysfunction and the diminished production of ATP in the frontal cortices or hippocampus of the adult rodents, and that improvement of mitochondrial function in brain improves the depression-like behavior. 11,21,34 Some studies from human and animals suggest that the deficiency of ATP resulting from mitochondrial disorders contributes to the pathogenesis of depression. It is widely known that ATP is mainly produced by aerobic and anaerobic glycolysis.…”
Section: Mitochondrial Energy Me Tabolis M and Depre Ss Ionmentioning
confidence: 99%
See 3 more Smart Citations